Analisis Kinerja Program Desa Berdaya di Kabupaten Mojokerto - Khoirun Nisak; Bambang Kusbandrijo (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2025)
As the smallest unit of government in promoting local economic growth, the village plays a crucial role; therefore, the government encourages sustainable village development based on local advantages, community participation, and economic empowerment—one of which is the Desa Berdaya Program implemented in Mojokerto Regency. The Desa Berdaya Program promotes village self-reliance by developing human potential and strengthening the local economy. The program’s success depends on the synergy between government policies, individual/team performance, and active community involvement to achieve the goal of independent and sustainable village development. This study aims to evaluate the implementation of the Desa Berdaya Program in Mojokerto Regency by examining the alignment between the planned initiatives and actual conditions in the field, as well as identifying the challenges that influence the program’s effectiveness. This study utilizes a qualitative descriptive approach, gathering data through observations, interviews, and document analysis. The data were processed through stages of collection, reduction, organization, and interpretation to draw conclusions. The results of the study indicate that the performance of the Desa Berdaya Program in Mojokerto Regency can be considered successful, yet improvements are needed for 2025–2026. The program’s success is influenced by performance management factors (Armstrong), including individual, leadership, team, system, and situational/contextual elements. The inhibiting factor lies in the limited capacity and understanding of individuals regarding the Desa Berdaya Program. Meanwhile, the supporting factors include bureaucratic leadership and effective team performance, attributed to good communication among members.